Copper and Zinc isotope signatures in scleratinian corals: Implications for Cu and Zn cycling in modern and ancient ocean. (15th January 2022) - Zhang, Ting; Sun, Ruoyu; Liu, Yi; Chen, Lu; Zheng, Wang; Liu, Cong-Qiang; Chen, Jiubin
Abstract: Metal stable isotopes in marine carbonates have been widely used as novel proxies for metal cycling through the geological past. Amongst these metals, copper (Cu) and zinc (Zn) have received great attention owing to their vital roles in metabolic processes. However, whether modern marine biogenic carbonates record the seawater isotope signatures of Cu (δ 65 Cu) and Zn (δ 66 Zn) and mechanisms and factors controlling isotope fractionation of these metals remain unclear, hindering applications of both isotope systems in paleoceanography. Here we present annually-resolved records of δ 65 Cu and δ 66 Zn in seven coral ( Porites ) cores sampled from different marine settings in the South China Sea and the Luzon Strait, western Pacific. We find that the aragonitic skeletons of corals are enriched in light Cu but heavy Zn isotopes relative to surface seawaters, with δ 65 Cu and δ 66 Zn in the range of −0.16 ± 0.06‰ to 0.40 ± 0.05‰ and 0.06 ± 0.04‰ to 0.46 ± 0.08‰ (2SD), respectively. The coral δ 65 Cu exhibits significant inter- and intra-colony variations, which are most likely controlled by Rayleigh-type fractionation in the calcifying fluids of corals rather than by changes in environmental factors or seawater δ 65 Cu. We thus suggest that δ 65 Cu in ancient carbonates may not be a direct record of Cu isotope compositions in coeval seawaters. In contrast, coral δ 66 Zn shows insignificant temporal variation, and the Zn isotope fractionation between individual corals and seawaters are relatively small and constant (0.10 ± 0.05‰, n = 33, 2SD). This limited Zn isotope fractionation is much lower than that determined during inorganic precipitation of calcite, which is likely due to pH up-regulation by the coral that changes aqueous Zn speciation, and preferential organic complexation of the heavy Zn isotopes in the calcifying fluids. Therefore, Porites corals are promising archives for tracking historical changes of surface seawater δ 66 Zn. Our new datasets of reef carbonates, particularly the coral δ 65 Cu values which are measured for the first time, could provide a better constrain on marine Cu and Zn geochemistry and their modern oceanic mass and isotope budgets.